Sobre cuadrados y rombos - Burrieza Muñiz, Alfredo; Yuste-Ginel, Antonio (UMA Editorial (Universidad de Málaga), 2025)
Modal logic is an active field of research that attracts the attention of scholars from quite diverse disciplines such as philosophy, linguistics, mathematics or computer sciences. These pages are intended to be the first open access basic textbook on modal logic written in Spanish. It is characterised by its introductory character, meaning that it has been designed to be comprehensible to any person with a minimal background in logic. Moreover, we have tried our best in making it a didactic writing, by filling some explicative gaps that more advanced books leave intentionally.